2012
DOI: 10.1590/s0004-282x2012001200006
|View full text |Cite
|
Sign up to set email alerts
|

Is the patent foramen ovale closure the best option?

Abstract: Patent foramen ovale (PFO) is a congenital heart disease remnant of fetal circulation. The flap of the foramen ovale (septum primum) closes against the atrial septum (septum secundum) and normally fuses within the first two years of life. If the septum secundum covers the oval foramen, but does not seal to the septum primum, then a probable PFO exists that can be "opened" by the Valsalva or other maneuvers that increase right atrial pressure 1,2 . Prevalence of incomplete fusion is approximately 25-27% 1,3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…Similar to cTTE, activated saline and VM were needed for this test. The VM was considered effective when there is a 25% decrease of MCA flow velocity (Zetola et al., ). The modified quantification criteria used were based on the Consensus Conference of Venice (Serena et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to cTTE, activated saline and VM were needed for this test. The VM was considered effective when there is a 25% decrease of MCA flow velocity (Zetola et al., ). The modified quantification criteria used were based on the Consensus Conference of Venice (Serena et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study from the same service evaluated 20 patients after surgical occlusion of the PFO and concluded that most of them would still have passage of a residual MES 01 year after occlusion. 20 Some advantages of TCD include the facts that it is a non-costly, non-invasive, and repeatable examination. 21 Since it is non-invasive, the exam can be performed without sedation, which allows for patient cooperation during the Valsalva maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…Inicialmente, eram utilizados dispositivos semelhantes aos de correção de comunicação interatrial e atualmente são usados dispositivos criados especificamente para fechamento do FOP. Além disso, o procedimento apresenta baixa morbi-mortalidade e uma alta taxa de sucesso 14,15 .…”
Section: Discussionunclassified